A Novel Organic Dopant for Spiro-OMeTAD in High-Efficiency and Stable Perovskite Solar Cells - Guo, Ying (Frontiers in Chemistry, 2022)
Perovskite solar cells (PSCs) have achieved excellent power conversion efficiencies (PCEs), however, there still exist some major challenges on device stability due to the hydrophilic Lithium bis((trifluoromethyl)sulfonyl)azanide (Li-TFSI), which is commonly introduced as a p-dopant to increase the hole mobility and conductivity of 2,2′,7,7′-tetrakis-(N,N-di-4-methoxyphenylamino)-9,9′-spirobifluorene (spiro-OMeTAD) hole transporting materials (HTMs). While ion migration, corrosiveness and hygroscopicity induced by the additive Li-TFSI is detrimental to the device stability, which significantly hinders further commercialization of PSCs. Herein, a hydrophobic organic ionic compound, trityltetra(pentafluorophenyl)borate (TPP) is explored as a novel efficient and stable alternative p-dopant, avoiding the long-term aging process for improving the conductivity of spiro-OMeTAD. As a result, the PSCs with TPP achieved a fill factor (FF) of 0.820 with an enhanced PCE of 23.03%, considerably higher than that of the Li-TFSI-doping device (22.39%) and comparable to Li-TFSI and Co-TFSI co-doped device (23.43%). The excellent performance with TPP may be associated with the higher work function of doped spiro-OMeTAD and a better alignment of energy levels with the valence band of perovskite, which substantially accelerates interfacial carrier transportation and minimize the open-circuit voltage (Voc) loss of PSCs. More importantly, the un-encapsulated TPP doped devices also display much superior operational stability under maximum power point (MPP) tracking with continuous light illumination in an ambient humid environment, which maintained 96-97% of the initial PCE over 1100 h outputting. Thus, this work will open up new possibilities for hydrophilic Li-TFSI dopant replacements.